2008
DOI: 10.4049/jimmunol.181.12.8624
|View full text |Cite
|
Sign up to set email alerts
|

Factor H Binding as a Complement Evasion Mechanism for an Anaerobic Pathogen, Fusobacterium necrophorum

Abstract: Fusobacterium necrophorum subspecies funduliforme is an obligate anaerobic Gram-negative rod causing invasive infections such as the life-threatening Lemierre’s syndrome (sore throat, septicemia, jugular vein thrombosis, and disseminated infection). The aim of our study was to understand if and how F. necrophorum avoids C activation. We studied 12 F. necrophorum subsp. funduliforme strains isolated from patients with sepsis. All strains were resistant to serum killing after a 1-h incubation in 20% serum. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The binding of fH SCRs 5-7 and 19 to 20 to Rck are analogous to those observed with Fusobacterium necrophorum (29) and Borrelia burgdorferi CspA (BbCRASP-1) (30), where the same regions of fH were responsible for binding to the pathogen surface. Binding of fH via a single or multiple SCRs from regions 5-7 or 19 to 20 has been observed in a diverse range of bacterial pathogens, such as S. pyogenes, B. afzelii, B. burgdorferi (30), P. aeruginosa (26), H. influenzae (25), N. gonorrheae (31), N. meningitidis (32) and Y. enterocolitica (28).…”
Section: Discussionmentioning
confidence: 52%
“…The binding of fH SCRs 5-7 and 19 to 20 to Rck are analogous to those observed with Fusobacterium necrophorum (29) and Borrelia burgdorferi CspA (BbCRASP-1) (30), where the same regions of fH were responsible for binding to the pathogen surface. Binding of fH via a single or multiple SCRs from regions 5-7 or 19 to 20 has been observed in a diverse range of bacterial pathogens, such as S. pyogenes, B. afzelii, B. burgdorferi (30), P. aeruginosa (26), H. influenzae (25), N. gonorrheae (31), N. meningitidis (32) and Y. enterocolitica (28).…”
Section: Discussionmentioning
confidence: 52%
“…pathogens, such as Fusobacterium necrophorum (28) and the yeast Candida albicans (29). In our experiments both CFHR4A and FH bound weakly to S. cerevisiae cells (supplemental Fig.…”
Section: Discussionmentioning
confidence: 55%
“…funduliforme isolates (34), but leukotoxin may not be present in all human invasive isolates (18). Friberg and coworkers showed that binding of factor H is important for complement evasion by the bacterium (8). However, the pathogenesis of the distinctive symptoms of Lemièrre's syndrome is unknown.…”
mentioning
confidence: 99%